Importance of Demography in Business Planning Regarding Nepal - Adhikari, Govinda Prasad (Voice of Teacher, 2022)
A business plan which has guided through several goals of the enterprise. The several elements of the business plan are directly linked with the demographic outputs of society. The objective of this study is to analyze the importance of demography in business planning. It also focused on the role of business statics in the business cycle. The information in this study has-been gathered from secondary sources. They are based on various reports, manuals, and guidelines from various organizations. Published articles, books, and reports. Information was analyzed in the descriptiv e method. Business demographic statistics help to identify the demographic outputs for the planning of the new business. It provides information on the creation, destruction, and survival of enterprises. The business demographic statistics provide information on the births and deaths of a business's plan. The growth of the country's population encourages competition in business activities. It further suggests expanding the market's potential. There is fundamental relationship between population and economic development. There was a fundamental relationship between the development and population, the demographic transition has a vital role in economic development. Therefore developed countries have relatively low fertility and mortality rates than developing countries. In the current year, Nepal is gaining its demographic dividend and is experiencing declining fertility, declining mortality rate, and increasing life expectancy. Nepal is passing with a bonus population which has a supportive role in expanding the national economy, new business, and finally national development of the country